Nonviral Delivery of CRISPR/Cas Systems in mRNA Format. Issue 11 (15th September 2022) - Liu, Zhen; Li, Zhenghua; Li, Bin
Abstract : The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated (Cas) genome editing system provides a powerful toolbox for genetic engineering. However, safe and efficient in vivo delivery of all CRISPR components into the nuclei of target organs remains challenging toward CRISPR/Cas clinical translation. With the rapid development of nanotechnology, the nonviral CRISPR/Cas mRNA delivery systems are emerging as one of the most clinically advanced platforms. CRISPR/Cas mRNA formulated in lipid nanoparticles is currently under clinical trials for treating hereditary transthyretin amyloidosis. Nonviral delivery of CRISPR/Cas systems in mRNA format not only minimizes immunogenicity and carcinogenicity, but also enables transient genome editing, thereby reducing potential off‐target effects. The recent advances in the nonviral CRISPR/Cas mRNA delivery systems should facilitate CRISPR technologies toward clinical applications. Abstract : Nonviral vectors hold promise for delivery of clustered regularly interspaced short palindromic repeats (CRISPR)/Cas systems in mRNA format. This review summarizes the recent advances in the nonviral CRISPR/Cas mRNA delivery systems and their applications in various diseases, emphasizing the biodistribution, gene editing efficiency, and therapeutic effects in vitro and in vivo.